Exploring university students’ perceptions and engagement in game-based learning - Hamadneh, Burhan; Fikry, Amr; Talaat, Mohammed; Abbas, Ahmed; Ghanem, Reham; Ramzy, Samah; Aly, Mohamed; Elkilani, Ahmed; Mabrouk, Sherin; Aloqlah, Reema (International Journal of Evaluation and Research in Education (IJERE), 2025)
Students in academia are facing serious challenges such as engagement, which causes academicians to question the quality and effectiveness of the teaching pedagogy. As such, new adapted innovative technological tools such as gamifications have been introduced to learning activities experiences and skills acquisition. However, little is known about the implementation of such technologies, which have been relatively underexplored in education literature. The primary objective of this study is to identify the perceptions of students and evaluate their engagement considering the use of gamification in the learning process. There were 210 respondents enrolled in the private university in Jordan were surveyed using a quantitative questionnaire. The study used descriptive statistics and independent sample t-test analyses on the data. The results indicated that the students have positive perceptions of game-based technology in both learning and classroom activity engagement. In addition, student perceptions and engagement did not differ significantly based on age or gender, but significant differences based on user experience were identified. These findings provide insight into the dynamic interaction between students and gamified technology to enhance student perceptions and promote meaningful learning. This research also provides implications on gamification literacy education and the pedagogically rich design of educational games to enhance student engagement. The recommendations are enumerated based on the obtained findings.